Erratum: Replication fork stability confers chemoresistance in BRCA-deficient cells - Chaudhuri, Arnab Ray; Callen, Elsa; Ding, Xia; Gogola, Ewa; Duarte, Alexandra A.; Lee, Ji-Eun; Wong, Nancy; Lafarga, Vanessa; Calvo, Jennifer A.; Panzarino, Nicholas J.; John, Sam; Day, Amanda; et al. (Nature (London), 2016)
Nature 535, 382–387 (2016); doi: 10.1038/nature18325 It has come to our attention that in this Article, owing to an error during the production process, ‘Brca2’ was mislabelled as ‘Brca1’ in Fig. 4b, and ‘Parp1’ was mislabelled as ‘Ptip’ in Fig. 4e. These errors have been corrected in the online versions of the paper.